Mucormycosis in the eastern mediterranean - Mokhbat, J. (2005)
Mucormycosis is a fairly rare fungal infection caused by ubiquitous fungi of the order Mucorales and primarily affects immunocompromised hosts. A series of 16 cases of invasive mucormycosis admitted to three referral centres in Beirut, Lebanon between 1981 and 1999 is described. It includes 12 patients with rhinocerebral, three with cutaneous, and one with pulmonary infection. Onset of symptoms occurred in the summer and autumn in 15 out of 16 patients, showing a statistically significant seasonal variation (P=0·007) A recent report of 19 patients from Tel Aviv describes a strikingly similar seasonal pattern. Studies on atmospheric concentration of Mucorales spores in the Eastern Mediterranean are lacking. Weather pattern analysis in Beirut revealed clustering of onset of invasive mucormycosis at the end of a dry, warm period, which begins around May and ends in October. Mucormycosis incidence appears to be seasonal in the Eastern Mediterranean.